Exploring work-family conflict among academics in Malaysia - Patel, Dhimir Rajendra Kumar (2015)
Work-family conflict (WFC) has been a consistent subject of concern for many employees in the modern economy. Scholars have explored this phenomenon in various conceivable dimensions in an attempt to assist employees with the important balancing act of their work and family life. While majority of previous studies has focused on gender, corporate and healthcare professionals, research among academics has been limited. This study explores the extent to which WFC exists among academics based in Malaysia. The study also investigates whether WFC impacts on the teaching performance on these academics, the salient factors that cause this circumstance and the strategies deployed by academics or institutions for mitigating WFC. Primary data was obtained qualitatively through semi-structured interviews conducted with 10 married academics (5 males and 5 females) from four different Private Higher Education institutes in Malaysia and who were either having or not having a child. Findings suggested that WFC definitely exists in the modern economy and academics understand WFC as a common concept with most descriptions parallel to present literature. In general, male academics continue to dominate in the work-to-family (WTF) path conflict while female academics lead in the family-to-work (FTW) path conflict and overall WFC is marginally higher for female academics than male academics. Academics with a child experience higher FTW path conflict while academics with no child experience higher WTF path conflict. For academics, WFC has an insignificant impact on their teaching performance but has a significant impact on their research publications which is an important finding and a contribution towards existing literature. Juggling between various work demands or family demands hinders their desire to produce adequate research papers that institutes value. WFC iv further results into adverse health consequences and positive or negative behavior outcomes. A number of personal strategies have been executed by academics to alleviate WFC with additional support from institutes. However, further implementation strategies of moderating WFC have been recommended by academics for institutes to seriously consider and assist academics in achieving the much anticipated balance between work and family life. This is an essential finding that contributes towards numerous studies in the WFC literature. This research has also made an important addition towards the unusual studies conducted in the Asian context over the several studies of WFC dominated by western contexts.